2020
DOI: 10.1021/acsomega.0c01659
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Stability of Actinium-225 Endohedral Fullerenes, 225Ac@C60

Abstract: We report the first synthesis of 225 Ac ( t 1/2 = 10 days) endohedral fullerenes, 225 Ac@C 60 . The 225 Ac@C 60 was produced with a 12 ± 2% efficiency by applying an electrical arc discharge between a source of α-particle emitter 225 Ac (∼1 mCi, electroplated on a Pt disk) and a thin coat of “preformed” C 60 on an Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Stability of catalysts might be improved, however, using C 60 as a carbon-based carrier model for loading of single-atom catalysts (SACs) because these reportedly appear to exhibit a boosted performance over typical SACs. [215][216][217][218]…”
Section: Insufficient Stabilitymentioning
confidence: 99%
“…Stability of catalysts might be improved, however, using C 60 as a carbon-based carrier model for loading of single-atom catalysts (SACs) because these reportedly appear to exhibit a boosted performance over typical SACs. [215][216][217][218]…”
Section: Insufficient Stabilitymentioning
confidence: 99%
“…Fullerene superatoms can serve as special building blocks for constructing nanomaterials due to their ability to encapsulate atoms or molecules. In 1985, Heath et al discovered the first stable embedded metal complex, LaC 60 , which was named metallofullerene . Since then, a rich variety of endohedral metallofullerenes (EMFs) with different cage sizes and embedded atoms have been extensively studied. Compared to larger-sized fullerenes, small fullerenes are relatively unstable due to increased curvature, causing strain within the cage and weakening π-conjugation. Especially for the smallest fullerene C 20 , which has all pentagonal faces, the bonds tend to be sp 3 bonds rather than the sp 2 bonds that are dominant in large fullerenes . Through metal doping, it is possible to increase the stability of smaller fullerenes and change their electronic properties. T. Guo et al reported in 1992 that the experiment of MC 28 confirmed that the 5f feature of U in the photoemission spectra of UC 28 existing in sublimed films is consistent with the formal 4 + valence state of U.…”
Section: Introductionmentioning
confidence: 99%